HUBUNGAN TINGKAT PENGETAHUAN, SIKAP DAN PERILAKUDENGAN KEJADIAN CHIKUNGUNYA DI DUSUNPRINGWULUNG, CONDONG CATURDEPOK SLEMAN - Uminingsih, Triana; Sekarwati, Novita (Jurnal Kesehatan Masyarakat, 2017)
ABSTRACT Background: Chikungunya is one disease should be noticed because its amount always rises. The amount of Chikungunya cases in Sleman regency were 344 cases in 2013, whereas in 2014 there were 253 cases and the highest case was 36 people at Pringwulung village, Condong catur, Sleman. Objective: To determine the relationship Relationship Level Knowledge, Attitude and Behavior with Genesis Chikungunya in Village Pringwulung, Condong Catur Depok Sleman. Methods: The design and type of research use analytic observational study with cross sectional design. The sampling technique used random sampling. Its population is the overall head of a family of 141 families, samples of 58 housewives. Data taken using a questionnaire. Bivariate analysis using the Chi-square test. Results: The results of correlation Chi Square test showed that the variable level of knowledge with Chikungunya obtained Sig = 0,001, variable attitude with Chikungunya obtained Sig = 0.009, and behavioral variables with the value obtained Chikungunya Sig = 0.029. Conclusion: There is a significant relationship between the level of knowledge, attitudes and behavior with Chikungunya in Village Pringwulung, Condong Catur Depok Sleman. Keywords: Knowledge, Attitude,Behaviour, and the Genesis Chikungunya